The attitude of junior secondary school students coming from families with alcohol problems to further education - Ławska, Wioletta; Braczkowski, Ryszard (Polish Journal of Public Health, 2009)
Introduction. The problem of addictions to various substances including alcohol is becoming more and more serious and widespread. To prevent this phenomenon, which has many victims and negatively infl uences young people’s lives, our society should be introduced with common knowledge on this type of addiction and its consequences. Aim. The aim of the thesis was to answer the following questions: Do teenagers from alcohol addicted families have problems at school? Are they ambitious enough to continue education? Are they aware of the problem of alcohol addition existing in their families? How does drinking problem infl uence the way children perceive their addicted parents? Material and methods. The research was done among junior secondary school students from Nowy Targ and the local area. Forty five (45) students were from alcohol addicted families and other 46 students were the part of the control group. The method used in the research consisted of an author’s questionnaire addressed to lower secondary school teenagers living in alcohol addicted families. Results. Children from alcohol addicted families have similar results at school to the children from the control group. The children from families with alcohol problems have good results at school and they are ambitious, however, as compared to their peers from the control group, they do not know whether they want to continue their education after leaving junior secondary school. Children from families with alcohol problems are aware of their parents’ addiction. Despite the problems mentioned previously the children from addicted families claim they feel happy. Alcohol addiction does not prevent the children from perceiving their parents as authority figures.